Athlete branding via social media: examining the factors influencing consumer engagement on Instagram. Issue 4 (4th July 2022) - Doyle, Jason P.; Su, Yiran; Kunkel, Thilo
ABSTRACT: Research Question : Social media platforms provide opportunities for athletes to promote their personal brands and attract engagement from consumers. Through this research, we examined the factors that influence social media engagement (likes and comments) with athlete content on Instagram. Research Methods : We monitored the posting habits of every MLS player with a public Instagram profile over a one-month period. In total, 1727 Instagram posts from 289 male professional athletes were included in the study. Drawing upon self-presentation theory, the Model of Athlete Brand Image, and relationship marketing, each post was dummy coded according to its content type and the overarching marketing orientation reflected by the characteristics of the post. Results and Findings : Results from ANOVA and hierarchical regression tests indicated the Athletic Performance content type attracted higher rates of consumer engagement than other content types. Posts containing good quality photos, and the athlete's teammates positively influenced engagement rates; whereas including hashtags negatively influenced engagement. Implications : Overall, this research extends knowledge surrounding athlete branding via social media and supports that impression management adopting a relationship marketing approach facilitates improved consumer engagement. Through this research we develop the Model of Athlete Branding via Social Media, which athletes and sport professionals can use to guide their social media strategy.